Fritação etnográfica : antropologia sobre o trance e os rolês de música eletrônica - Souza, Anatil Maux de (2020)
Considering the universe of electronic music in the metropolitan region of Aracaju (SE), this dissertation crosses the productions of worlds that arises in the relationships around experiences with electronic trance music, temporalities, anthropology, psychoactive substances and young people. This is a study carried out with regulars, DJs and people interested in electronic music and / or parties along the lines of what is meant by rave today. Thus, I understand that making use of ethnographic sensitivity aims at political issues and ways of building relationships with the empirical field. From collective experiences, participation in festive events, involvement in cyberspace and access to other states of consciousness, it is clear that the practical path of scientific work presents techniques based on specific senses, whether in uninterrupted dance, drug use or immersion. sonorous. In this way, the research exists in the intention of engagement that comes up against the discomfort that the raves generate, especially in what the illicit substances produce, bearing in mind, therefore, that what drives their practices are constructions of intentionalities. Taking into account the agency of the interlocutors in their socio-cultural layers, it is possible to understand the circuit of cultural production; the uses of psychoactive and teachings of (self) care; body handling and symbolic extension in everyday life. Such a way of celebrating, therefore, inscribes the formation of “scenes” throughout the experiences (with drugs) and points to possibilities of arrangements of ideas that appear discontinuously to the actions of public policies and health care practices.